Comparison of trimethylgallium and triethylgallium as Ga source materials for the growth of ultrathin GaN films on Si (100) substrates via hollow-cathode plasma-assisted atomic layer deposition - ALEVLİ, MUSTAFA (A V S AMER INST PHYSICS, 2016)
GaN films grown by hollow cathode plasma-assisted atomic layer deposition using trimethylgallium (TMG) and triethylgallium (TEG) as gallium precursors are compared. Optimized and saturated TMG/TEG pulse widths were used in order to study the effect of group-III precursors. The films were characterized by grazing incidence x-ray diffraction, atomic force microscopy, x-ray photoelectron spectroscopy, and spectroscopic ellipsometry. Refractive index follows the same trend of crystalline quality, mean grain, and crystallite sizes. GaN layers grown using TMG precursor exhibited improved structural and optical properties when compared to GaN films grown with TEG precursor. (C) 2015 American Vacuum Society.
Keywords: PULSED-LASER DEPOSITION; SAPPHIRE